2019
DOI: 10.1007/s00415-019-09620-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arterial pulsatility is associated with features of small vessel disease in patients with acute stroke and TIA: a 4D flow MRI study

Abstract: Cerebral small vessel disease (SVD) is a major cause of stroke and cognitive impairment. However, the underlying mechanisms behind SVD are still poorly understood. High cerebral arterial pulsatility has been suggested as a possible cause of SVD. In population studies, arterial pulsatility has been linked to white matter hyperintensities (WMH), cerebral atrophy, and cognitive impairment, all features of SVD. In stroke, pulsatility data are scarce and contradictory. The aim of this study was to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 43 publications
(71 reference statements)
2
34
1
Order By: Relevance
“…The pathogenesis role of increased pulsatility in intracranial small vessels disease has also been revealed by studies measuring cerebrovascular pulsatility directly. 28,29 Of note, although endothelial dysfunction has been suggested as a key early step in the pathophysiology of atherosclerosis, 30 we did not find an association with intracranial atherosclerosis in our study. The reason for this might be that the small numbers of subjects having plaque in a relatively healthy study population limit the power to detect a significant association.…”
Section: Discussioncontrasting
confidence: 72%
“…The pathogenesis role of increased pulsatility in intracranial small vessels disease has also been revealed by studies measuring cerebrovascular pulsatility directly. 28,29 Of note, although endothelial dysfunction has been suggested as a key early step in the pathophysiology of atherosclerosis, 30 we did not find an association with intracranial atherosclerosis in our study. The reason for this might be that the small numbers of subjects having plaque in a relatively healthy study population limit the power to detect a significant association.…”
Section: Discussioncontrasting
confidence: 72%
“…Birnefeld et al. 16 examined the ICAs and MCAs (M1, M3) of 89 patients with acute ischaemic stroke or transient ischaemic attack (divided into two groups based on clinical assessment: those with associated cerebral small vessel disease (SVD) and those without). They found ICA pulsatility to be associated with increased white matter lesion volume and M1 pulsatility with decreased cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…Holmgren et al 34 demonstrated the technique's ability to measure arterial pulsatility and compliance, and cerebrovascular resistance, across a range of cerebral arteries in a population of elderly subjects (mean 79 AE 5 years). Birnefeld et al 16 examined the ICAs and MCAs (M1, M3) of 89 patients with acute ischaemic stroke or transient ischaemic attack (divided into two groups based on clinical assessment: those with associated cerebral small vessel disease (SVD) and those without). They found ICA pulsatility to be associated with increased white matter lesion volume and M1 pulsatility with decreased cognitive function.…”
Section: Brain Ageing and Cerebral Small Vessel Diseasementioning
confidence: 99%
“…MRI phase contrast images were processed using the scanner software (Siemens Syngo) by manually placing a region of interest around the middle cerebral artery and quantifying the flow. The MRI pulsatility index, PI MRI , was then obtained by subtracting the minimum flow from the maximum flow and dividing it by the mean flow over the cardiac cycle [14]; i.e.,…”
Section: Calculating the Indices Mri Pulsatility Indexmentioning
confidence: 99%